AB0215 The Combination of Methotrexate with Hydroxychloroquine Is More Effective than Monotherapy in Early Rheumatoid Arthritis: A Quasi-Experiment. (15th July 2016) - Gevers, L.A.H.A.; van den Hombergh, W.M.T.; Schipper, L.G.; Meek, I.L.; Fransen, J.
Abstract : Background: A tight-control strategy starting with a combination of methotrexate (MTX) and hydroxy-chloroquine (HCQ) was implemented between 2010–2015 in our clinic; without evidence from RCTs for the combination of MTX with HCQ in early RA (1). Some physicians chose not to adhere to this combination, which post-hoc gave the opportunity for a quasi-experiment. Objectives: To investigate the effect of starting with MTX + HCQ combination therapy, versus MTX or HCQ mono therapy, on the DAS28 at 6 and 12 months in patients with early RA, while treating to the target of remission (DAS28 <2.6). Methods: All patients with early RA (ACR-EULAR criteria) between April 2010 and October 2015 were eligible. Two sub cohorts were formed according to whether the treatment was started with MTX+HCQ as intended, or with MTX or HCQ. There were n=50 patients in the adherent-group and n=38 patients in the non-adherent group who were initially treated with MTX or HCQ mono therapy (sometimes with addition of the other drug after more than four weeks). The primary outcome was the ΔDAS28 at 6 months. Results: In the study period 176 RA patients were treated and 88 could not be included due to lack of follow-up data. At baseline, there were no large or significant (p<0.05) differences between MTX+HCQ and mono therapy groups regarding age (mean 57 years), gender (73% female), disease duration (median 21 weeks). Also, rheumatoid factor positivity (48% and 34%), mean baseline DAS28 (4.3 (1.3) and 4.2 (1.1)) were not different (p>0.05) between MTX+HCQ and mono therapy groups. In the mono therapy group, 30 patients started with MTX and 8 started with HCQ. After 6 months, the DAS28 decreased – 1.4 in the MTX+HCQ group and – 0.8 in the non-adherent group (p=0.044). After 12 months, the DAS28 decreased – 1.7 in the MTX+HCQ group and – 0.8 in the non-adherent group (p=0.007). After 12 months, 48% of adherent patients were in DAS28 remission compared to 26% of non-adherent patients (p=0.039). There were no baseline confounders operational. Conclusions: In early RA starting with MTX and HCQ combination therapy leads to a larger decrease in DAS28 after 6 and 12 months and higher percentages of remission after 12 months in comparison with mono therapy with MTX or HCQ. References: Ma MH, Kingsley GH, Scott DL. A systematic comparison of combination DMARD therapy and tumour necrosis inhibitor therapy with methotrexate in patients with early rheumatoid arthritis. Rheumatology (Oxford, England). 2010;49(1):91–8. Disclosure of Interest: None declared